PENYELESAIAN SISTEM PERSAMAAN LINIER ATAS ALJABAR MAX-PLUS DAN APLIKASINYA MENGGUNAKAN VISUAL STUDIO - Doberhol, James; Suroto, Suroto; Guswanto, Bambang Hendriya (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2024)
Determining solution of the system of linear equations over max-plus algebra cannot be done as in linear algebra, since its algebraic structure is a semifield. In this article, we discuss determining solution of the system of linear equations over max-plus algebra and designing the application using Visual Studio. The solution of the system of linear equations is carried out using a difference matrix and a reduction matrix that obtained from the coefficient matrix and constant matrix of the system of linear equations. Then, the process of determining this solution is designed in the application using Visual Studio. The results obtained are a step procedure for solving a system of linear equations over max-plus algebra as outlined in the application using Visual Studio